METHODOLOGY OF TRAINING FOR DEVELOPING SPEAKING AND EXECUTIVE COMPETENCE OF STUDENTS OF GRADE 5-7 IN A LITERARY LABORATORY - Nurmuhammadov Jamoliddin Shermuhammad ogli (Scholar Express Journal, 2023)
This article reflects the problems and solutions of organizing activities that develop the speech and performance potential of 5th-7th grade students in a literary laboratory. In creating an audio book, it is intended to use the students' speech abilities correctly. Expressive reading techniques for the development of executive potential are explained through special tables. Literary textbooks also talk about the ways to record and decorate works of art given as educational texts in the form of audio books. In the article, examples for reading and writing from 5th-6th-7th grade literature textbooks are cited
Keywords: literary laboratory; literary education; audiobook